Women Entrepreneurs and Access to Microfinance : A Pathway to Economic Empowerment (Universitas Kristen Indonesia Toraja, 2023)
This study evaluates the role of microfinance in empowering women entrepreneurs in developing countries. It examines the challenges women face in accessing financial services, the impact of microloans on business growth, and the socio-economic benefits of financial inclusion. The paper also highlights successful microfinance models and offers policy recommendations to promote gender equality in entrepreneurship.